Ways to hold national action games with kindergarten children - A.Sh.Usmonov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
According to the content of preschool pedagogy, kindergartens and the requirements of physical education, children of kindergarten age are divided into different age groups and are called small, medium and large groups